2017
DOI: 10.1016/j.mod.2017.04.157
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric position of the germinal vesicle and cortical flow during oocyte maturation specify the animal-vegetal axis of ascidian embryos

Abstract: The animal-vegetal (A-V) axis is already set in unfertilized eggs. It plays crucial roles in coordinating germ-layer formation. However, how the A-V axis is set has not been well studied. In ascidians, unfertilized eggs are already polarized along the axis in terms of cellular components. This polarization occurs during oocyte maturation. Oocytes within the gonad have the germinal vesicle (GV) close to the future animal pole. When the GVs of full-grown oocytes were experimentally translocated to the opposite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Embryogenesis typically begins by reorganizing the cytoplasm within the oocyte (ooplasm). Seminal studies in tunicates have shown that the segregation of maternal determinants within the oocyte establish the blueprint for embryo patterning (Wilson, 1900;Satoh, 1994;Prodon et al, 2008Prodon et al, , 2009Nishida et al, 2017). Subsequent work in both vertebrate and invertebrate model organisms has demonstrated a common and essential role of ooplasmic reorganization for oocyte maturation and embryo patterning (Schuh and Ellenberg, 2008;Nance et al, 2003;Nance and Zallen, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryogenesis typically begins by reorganizing the cytoplasm within the oocyte (ooplasm). Seminal studies in tunicates have shown that the segregation of maternal determinants within the oocyte establish the blueprint for embryo patterning (Wilson, 1900;Satoh, 1994;Prodon et al, 2008Prodon et al, , 2009Nishida et al, 2017). Subsequent work in both vertebrate and invertebrate model organisms has demonstrated a common and essential role of ooplasmic reorganization for oocyte maturation and embryo patterning (Schuh and Ellenberg, 2008;Nance et al, 2003;Nance and Zallen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the nematode Caenorhabditis elegans, for instance, cortical actomyosin network flows are required for anterior-posterior polarization by accumulating cortex associated polarization cues at the anterior pole of the oocyte and zygote (Nance et al, 2003;Munro et al, 2004). Likewise in ascidians, cortical actomyosin flows are critical for germ layer specification by driving the segregation of maternal determinants within the oocyte (Prodon et al, 2008;Nishida et al, 2017). Finally, in starfish oocytes, periodic cortical actomyosin contraction waves trigger ooplasm flows by dynamically changing oocyte shape (Klughammer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%